Pengujian Kompos Limbah Media Baglog Jamur dan Biochar Cangkang Kernel Kelapa Sawit pada Bibit Okulasi Karet (Hevea Brasiliensis) yang Ditumpangsari dengan Tanaman Padi - Fajar Wihono; Sumihar Hutapea; Gusmeizal Gusmeizal (Jurnal Ilmiah Pertanian ( JIPERTA), 2020)
Testing of Compost Waste Baglog Media Fungus and Biochar Palm Kernel Shells in Rubber Grafting Seeds (Hevea Brasiliensis) intercropped with Rice Plants. This thesis is under the guidance of Ir. Gusmeizal, MP as supervisor I and Dr.Ir. Sumihar Hutapea MS, as supervisor II This research was conducted in Sampali Village, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra, on May 28-September 8, 2018. The research method used was a factorial randomized block design (RAK) consisting of 2 treatment factors, namely, mushroom baglog compost media waste (K) and oil palm kernel biochar (B) where compost treatment was 3 levels and oil palm kernel biochar treatment was 4 level. Factor I: Compost of mushroom baglog media waste with 3 levels of concentration ie K0 = Control (without compost), K1 = Baglog compost of 50 grams / polybag, K2 = Baglog compost of 100 grams / polybag. While Factor II: Biochar palm kernel with 4 levels, namely: B0 = Control (without Biochar), B1 = Giving Biochar Palm Kernel 10 grams / polybag, B2 = Giving Biochar Palm Kernel 20 grams / polybag, B3 = Giving Biochar Kernel 10 grams / polybag, B2 = Giving Biochar Palm Kernel 20 grams / polybag, B3 = Giving Biochar Kernel Palm Oil 30 grams / polybag, each treatment was repeated 3 times.The parameters observed in this study consisted of shoot bud rupture time, shoot height (cm), number of strands (leaves), leaf area, leaf color, stem diameter. The results showed that the treatment given had no significant effect on all parameters.